America - Kafka, Franz, 1883-1924.; Vintage Books (London : Vintage Books, 2005)
The story of land-surveyor K's obsessive attempts to reach the castle, illustrating man's struggle against bureaucracy.
Adult
Translated from the German.
Keywords: Castle -- Fiction; Surveyors -- Fiction; Bureaucracy -- Fiction